Particle swarm optimization of a Small modular reactor fuel assembly design with composed of U-ZR plates and MOX pins, based on Radkowsky concept - Laranjo de Stefani, Giovanni; dos Santos, Thiago Augusto; de Albuquerque, Arthur Leal; Artuso Miranda, Roberto Junior; da Silva, Marcelo Vilela; Nicolao Carneiro, José Rafael; de Aguiar Oliveira, Maria Vitória; Schirru, Roberto (Progress in nuclear energy (New series), 2026)
This work proposes a fuel assembly design based on the Seed-Blanket Unit (SBU) concept, characterized by two distinct regions: Uranium plates in the central region (seed) to enhance neutron leakage and the surrounding region (blanket) consists of mixed oxide fuel rods composed of thorium and uranium, as originally proposed by Radkowsky. This configuration leverages the advantages of enhanced safety, improved efficiency, and greater resistance to nuclear proliferation. An innovation introduced in this study is the integration of two different geometries within a single fuel assembly: plate-type elements in the seed region—favoring increased neutron leakage—and cylindrical rods in the blanket region—minimizing neutron leakage. This hybrid geometry aims to optimize the neutron economy by enhancing fissile material breeding while controlling neutron losses. The main objective of this research is to investigate the viability and neutronic performance of a novel multigeometry fuel assembly—featuring a thorium-based blanket and a metallic uranium seed—by using Particle Swarm Optimization (PSO) as a computational tool to determine optimal design parameters. The goal is to maximize the in-core breeding of U-233, thereby extending fuel cycle longevity, reducing reliance on enriched uranium, minimizing plutonium generation, and lowering the radiotoxicity and decay heat of spent fuel. Neutronic simulations were carried out using the SERPENT 2.1.30 Monte Carlo code. To couple SERPENT with the PSO algorithm, a Python-based interface was developed to automatically update input parameters and generate simulation files within predefined value ranges. The optimization process was successful, yielding a fuel assembly with a 25.40 % higher conversion factor compared to a reference configuration at the end of the burnup cycle. Additionally, the optimized assembly achieved the production of 2.08 kg of U-233 over a burnup period exceeding 550 effective full-power days (EFPDs). •Hybrid fuel assembly: seed plates and thorium–uranium rods in one design.•Particle swarm optimization applied to nuclear reactor design parameter optimization.•Conversion ratio improves by about 25 % over reference at end of cycle.•Produces 2.08 kg of uranium-233 in over 550 days.•About 40 % less plutonium formed than in the reference assembly.